PENDERITAAN AYUB: PRATRAGEDI, TRAGEDI DAN PASCAPEMULIHAN - Sin, Sia Kok (Sekolah Tinggi Teologi Aletheia, 2026)
AbstractThe Book of Job is a book about suffering, centered on its main character, Job, a righteous man who experiences great suffering. Scholars generally discuss Job’s extraordinary pre-tragedy condition, the intense suffering after the tragedy, and the improved condition following God's restoration. However, scholars have paid less attention to Job’s suffering before the tragedy and after the restoration. Using a psychological approach, this article aims to complement previous studies by exploring Job’s suffering both before the tragedy and after his restoration. The author argues that even before the tragedy, Job had to endure a certain kind of hardship or suffering, as his